Effect of Drainage and Subgrade Compaction on Pavement Frosting Performance in Construction Zone - Khabiri, Mohammad Mehdi (International Journal of Sustainable Construction Engineering and Technology, 2018)
The roughness in the construction site surrounding condition and the pavement of the paths of the workzones makes a decrease in the efficiency in executive operation. Increasing the rolling resistance due to the roughness, is one of the reasons for reducing the speed of operation and delay in that. In this study first, the fields of roughness appearance are recognized including inflation due to frost of subgrade and executive operations areas, then frost depth are calculated which is affected by the density conditions and moisture amount of workzone area’s surface. The different percentages of moisture 2, 5, 7, 15 and 20 and compaction ratio 100, 90, 75, 65 percent were considered in this study for density of workzones' top surface. Frost depth calculations are carried out in the US - Army method and by Pavem-Calc software. The results show that an increase in the density of 40 % is caused by a 25 % increase in frozen strain. Furthermore, the increase of 15 % of pavement moisture causes a 20 % increase in the frost depth and the increase of surface roughness. Statistical analyses were carried out to investigate the effectiveness of the research variables and the classification of results in the classification method of CART algorithm.